Analysis Of The Influence Of Profitability, Leverage And Liquidity On Company Value (Case Study on the listed Food and Beverage Industry Sub-Sector on the Indonesia Stock Exchange for the period 2018-2022) - Dian Setia Rini; Agtovia Frimayasa (Sean Institute, 2023)
This study aims to examine the factors that influence firm value. There are several factors used, including profitability, leverage, liquidity. The purpose of this study was to test empirically whether profitability, leverage, liquidity influence firm value in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The study experienced a fluctuating phenomenon in food and beverage sub-sector companies listed on the IDX in 2018-2022. The population used as the research object is 26 food and beverage sub-sector companies listed on the Indonesia Stock Exchange in the 2018-2022 period. The determination of the research sample used the purposive sampling method and obtained a sample of 9 food and beverage sub-sector companies based on certain criteria. The results show that profitability has an effect on firm value, leverage and liquidity have no significant effect on firm value. In this study there are still many limitations and shortcomings, namely, the effect of the independent variable on the dependent is only able to explain 64.4%, so it is necessary to add other independent variables.